2021
DOI: 10.1038/s41598-021-89402-1
|View full text |Cite
|
Sign up to set email alerts
|

Human monocyte-derived type 1 and 2 macrophages recognize Ara h 1, a major peanut allergen, by different mechanisms

Abstract: Evidence has suggested that major peanut allergen Ara h 1 activates dendritic cells (DCs) via interaction with DC-SIGN (dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin), a C-type lectin receptor, and contributes to development of peanut allergy. Since macrophages, as well as DCs, play a crucial role in innate immunity, we investigated whether natural Ara h 1 (nAra h 1) activates two different subsets of macrophages, human monocyte derived macrophage type 1 (hMDM1: pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Natural Ara h 1 carries high mannose (Man5GlcNAc2 and Man6GlcNAc2) and nonfucosylated complex N-glycans (Man4XylGlcNAc2 and Man3XylGlcNAc2) [ 207 ]. Studies have shown that such carbohydrate residues bind to DC-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN) or Scavenger receptor A (SR-A) and thus activate human monocyte-derived DC and macrophages [ 208 , 209 ]. Beta-conglycinin also carries N-linked glycans comprising 77% mannose and 23% N-acetylglucosamine, and thus might have the intrinsic immunogenicity to stimulate macrophages and DCs like peanut 7S globulin [ 210 ].…”
Section: Cholesterol Lowering Dietary Compoundsmentioning
confidence: 99%
“…Natural Ara h 1 carries high mannose (Man5GlcNAc2 and Man6GlcNAc2) and nonfucosylated complex N-glycans (Man4XylGlcNAc2 and Man3XylGlcNAc2) [ 207 ]. Studies have shown that such carbohydrate residues bind to DC-specific intercellular adhesion molecule-3 grabbing nonintegrin (DC-SIGN) or Scavenger receptor A (SR-A) and thus activate human monocyte-derived DC and macrophages [ 208 , 209 ]. Beta-conglycinin also carries N-linked glycans comprising 77% mannose and 23% N-acetylglucosamine, and thus might have the intrinsic immunogenicity to stimulate macrophages and DCs like peanut 7S globulin [ 210 ].…”
Section: Cholesterol Lowering Dietary Compoundsmentioning
confidence: 99%
“…8 At present, research on allergies caused by various food proteins mainly focuses on the mechanism of food allergies. 9,10 The difference and severity of allergy symptoms caused by these food proteins is still not well understood. Interestingly, Mondoulet et al studied CD62L + Tregs isolated from mice treated with milkepicutaneous immunotherapy (EPIT), and found that mice with CD62L + Treg transfer before peanut sensitization were protected from anaphylaxis as compared with an allergic group.…”
Section: Introductionmentioning
confidence: 99%